The Impact of Parental Incarceration on the Physical and Mental Health of Young Adults - Lee, Rosalyn D. (American Academy of Pediatrics, 2013)
OBJECTIVES: We investigated the relationship between parental incarceration history and young adult physical and mental health outcomes using Wave 1 and Wave 4 data from the National Longitudinal Study of Adolescent Health. METHODS: Dependent variables included self-reported fair/poor health and health diagnoses. The independent variable was parental incarceration history. Cross-tabulations and logistic regression models were run. RESULTS: Positive, significant associations were found between parental incarceration and 8 of 16 health problems (depression, posttraumatic stress disorder, anxiety, cholesterol, asthma, migraines, HIV/AIDS, and fair/poor health) in adjusted logistic regression models. Those who reported paternal incarceration had increased odds of 8 mental and physical health problems, whereas those who reported maternal incarceration had increased odds of depression. For paternal incarceration, with the exception of HIV/AIDS, larger associations were found for mental health (odds ratios range 1.43–1.72) as compared with physical health (odds ratios range 1.26–1.31) problems. The association between paternal incarceration and HIV/AIDs should be interpreted with caution because of the low sample prevalence of HIV/AIDs. CONCLUSIONS: This study suggests exposure to parental incarceration in childhood is associated with health problems in young adulthood. Extant literature suggests underlying mechanisms that link parental incarceration history to poor outcomes in offspring may include the lack of safe, stable, nurturing relationships and exposure to violence. To prevent poor health in offspring of the incarcerated, additional studies are needed to (1) confirm the aforementioned associations and (2) assess whether adverse experiences and violence exposure in childhood mediate the relationship between parental incarceration history and offspring health problems.